Stage at Diagnosis of Stomach Cancer Amongst Selected East African Countries: A Mini Systematic Review - Cyuzuzo Callixte; Dwi Sutiningsih; Suhartono Suhartono; Selamat Budijitno (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2023)
Background: Stomach cancer is one of the leading cause of death globally due to its ability to hide clinical manifestations at early stage. This review was mainly aimed to assess the stage at diagnosis of the stomach malignancy among the selected East African countries.Methods: In this review, we retrieved 61 resources composed of 57 papers and 4 reports that were published between the year of 2005 and 2023, however only 22 papers that satisfy the inclusion criteria were considered.Result: The results revealed of this review disclosed that the stomach cancers are diagnosed at advanced stages, specifically stage III and stage IV and this was found to negatively affects the patients’ clinical outcomes and overall survival rate.Conclusion: The present review concludes that the stomach cancer cases that are diagnosed in the selected East African countries are diagnosed late and recommend early diagnosis, improvement of health facilities and diagnostic modalities and capacity development of the oncologists, cancer focal persons and other health professionals.